HUMANISTIC WORLD VIEW AND ITS TYPES - Dilrabo Talabova (Scholar Express Journal, 2023)
The idea of humanism has been studied since ancient times in the countries of Europe and the East. In both regions, the idea of humanism was treated as a national and universal value. American researcher Warren Allen Smith put forward the idea of grouping the humanistic worldview. When studying the content of the researcher's approach, a one-sided approach to the grouping of the humanistic worldview is noticeable. Therefore, in the process of conducting the study, the humanistic worldview was grouped on the basis of the author's approach. The article is about this grouping
Keywords: Humanism; humanistic worldview; types of humanistic worldview